Effectiveness of humor content marketing in driving consumer engagement among Generation Z in Facebook - Alcantara, Pia Marie L. Araza, Loraine Claire G. Balboa, Angelika Mel L. Barrozo, Elisah Joyce S. Cepe, Chrisella Jane R. Gregorio, Dhana Kristel V. Lopez, Reya, Wynette M. Nepomuceno, Janeth V. Pabustan, Hannah Mariz B. Tolosa, Jaybe N. 4 0 16; 5
ABSTRACT The study aimed to evaluate the effectivermos of applying humor content Facebook to drive consumer engagement among Generation 2 students of Pamantasan ng Lungsod ng Maynila under the College of Business Administration in answering this, the researchers intended to figure out whether there is a significant relationship between the consumers level of perception of humor and the level of engagement in social media In this study, non-experimental correlations research design was used. The researchers used non-probability sampling, and the respondents were selected based on the characteristics that are relevant to the aims of the study. The survey was conducted online, and the statistical methods used to draw an exact interpretation of the data gathered were percentage, weighted mean, and Pearson's Correlation Coefficient (R). It was concluded in the study that there is a high positive correlation between the consumers' level of feeling of humor and level of engagement in social media which means that applying humor in Content Marketing can be effective. Moreover, the implications on the theories used-Humor Message Taxonomy and Uses and Gratification Theory-were proved to be correct and can still be applied up to this time. With this study, fast-food companies in the Philippines may use and utilize the application of humor in Content Marketing as a tool to drive engagement. However, the content of humor should be taken into consideration as humor is subjective and cannot be applied to all situations and any type of consumers. Keywords: Humor, Consumer Engagement, Content Marketing
Business Research: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2